Khả năng sử dụng silicagen như chất mang xúc tác trong phản ứng oxi hóa phenol - Vân, Đỗ Khánh; Thắng, Vũ Đào; Yêm, Hoàng Trọng (Vietnam Journal of Chemistry, 2014)
This paper presents the results of study the ability of silicagel as support-substance of catalysts in the phenol oxidation reaction. Silicagel have positive effect in the phenol oxidation reaction if diameter of pore approximately 46 - 70 Å. With silicagel as support-substance Me(acac)nhave shown very good activity in the phenol conversion 100%. The products were almost acetic acid.